ENHANCING PRIMARY STUDENTS' READING SKILLS THROUGH AUGMENTED REALITY-ENRICHED TURKISH TEXTS - Dindas, Serhat; Ince, Murat (SCIENTIA SOCIALIS, 2025)
The present study examined whether the integration of augmented reality (AR) into fourth-grade Turkish reading lessons enhances students' reading comprehension and motivation. A quasi-experimental pretest-posttest control group design was employed, involving 48 students (24 experimental and 24 control) from a public primary school. Students in the experimental group engaged with AR-enriched texts, while the control group read the same texts without AR enhancement. Reading comprehension proficiency and attitudes towardAR were measured using standardized scales, and qualitative interviews were conducted to gather student feedback. Results indicated that the experimental group demonstrated a significant improvement in reading skill scores compared to their baseline, while the control group showed no significant progress. A moderate positive correlation was observed between students'reading comprehension self-efficacy and their attitudes towards AR, indicating that students who felt more confident in their reading skills also tended to viewAR-based learning more positively. Qualitative findings further revealed thatAR enriched texts increased student engagement-evoking curiosity, excitement, and enjoyment-and helped students maintain focus during reading. These results suggest that integrating AR into reading activities can enhance elementary students' reading abilities and motivation. These findings highlight the potential of integrating AR into literacy education to foster students' engagement and comprehension. The study underscores the importance of designing technology-supported reading activities that align with curriculum goals and suggests thatAR can serve as an effective educational tool to enhance motivation and learning outcomes in primary education.
Keywords: augmented reality; reading skills; primary education; educational technology; EDUCATION; Education & Educational Research